Responses of Unimpaired Flows, Storage, and Managed Flows to Scenarios of Climate Change in the San Francisco Bay‐Delta Watershed. Issue 10 (12th October 2018) - Knowles, N.; Cronkite‐Ratcliff, C.; Pierce, D. W.; Cayan, D. R.
Abstract: Projections of meteorology downscaled from global climate model runs were used to drive a model of unimpaired hydrology of the Sacramento/San Joaquin watershed, which in turn drove models of operational responses and managed flows. Twenty daily climate change scenarios for water years 1980–2099 were evaluated with the goal of producing inflow boundary conditions for a watershed sediment model and for a hydrodynamical model of the San Francisco Bay‐Delta estuary. The resulting time series of meteorology, snowpack, unimpaired flow, reservoir storage, and managed flow were analyzed for century‐scale trends. In the Sacramento basin, which dominates Bay‐Delta inflows, all 20 scenarios portrayed warming trends (with a mean of 4.1 °C) and most had precipitation increases (with a mean increase of 9%). Sacramento basin snowpack water equivalent declined sharply (by 89%), which was associated with a major shift toward earlier unimpaired runoff timing (33% more flow arriving prior to 1 April). Sacramento basin reservoirs showed large declines in end‐of‐September storage. Water‐year averaged outflows increased for most scenarios for both unimpaired and impaired flows, and frequency of extremely high daily unimpaired and impaired flows increased (increases of 175% and 170%, respectively). Managed Delta inflows were projected to experience large increases in the wet season and declines in the dry season. Changes in management strategy and infrastructure can mitigate some of these changes, though to what degree is uncertain. Key Points: Projections of reservoir storage and managed flows under an ensemble of climate‐change scenarios are presented Declining snowpack and shifting precipitation patterns lead to projected increases in extreme flows and earlier annual runoff Managed Delta inflows are projected to experience large increases in the wet season and declines in the dry season